2021
DOI: 10.1002/anie.202110019
|View full text |Cite
|
Sign up to set email alerts
|

A New Dioxazolone for the Synthesis of 1,2‐Aminoalcohols via Iridium(III)‐Catalyzed C(sp3)−H Amidation

Abstract: Vicinal aminoalcohols are widespread structural motifs in bioactive molecules.W er eport the development of anew dioxazolone reagent containing ap-nitrophenyldifluoromethyl group,which1.displays agood safety profile;2.shows ar emarkably high reactivity in the oxime-directed iridium-(III)-catalyzed amidation of unactivated C(sp 3 ) À Hb onds;3 . leads to amide products whichc an be hydrolyzed under mild conditions.T he amidation reaction is mild, general and compatible with both primary CÀHb onds of tertiary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…In recent decades, considerable attention has been paid to 1,2‐aminoalcohols, [1–5] 1,3‐aminoalcohols, [6–8] and 3‐amino‐1,2‐diols, [9–14] with the latter combining the chemical properties of 1,2‐ and 1,3‐aminoalcohols. These compounds play a crucial role in numerous branches of human life sciences.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, considerable attention has been paid to 1,2‐aminoalcohols, [1–5] 1,3‐aminoalcohols, [6–8] and 3‐amino‐1,2‐diols, [9–14] with the latter combining the chemical properties of 1,2‐ and 1,3‐aminoalcohols. These compounds play a crucial role in numerous branches of human life sciences.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, two main types of transformations, C–H activation 2–4 and nitrene insertion, 5–9 have been developed with transition-metal catalysts and activated amidating reagents (Scheme 1). For instance, dioxazolones were employed as an effective amide source in transition metal (Rh, Co, and Ir)-catalyzed sp 3 C–H activation by Li, 2 Seayad, 3 and Baudoin 4 (Scheme 1a). Nitrene insertion was demonstrated as another important strategy for direct C(sp 3 )–H amidation with various catalysts (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular C(sp 3 )-H amidation has emerged as an appealing approach for accessing diversely functionalized amides. In this field, two main types of transformations, C-H activation [2][3][4] and nitrene insertion, [5][6][7][8][9] have been developed with transition-metal catalysts and activated amidating reagents (Scheme 1). For instance, dioxazolones were employed as an effective amide source in transition metal (Rh, Co, and Ir)-catalyzed sp 3 C-H activation by Li, 2 Seayad, 3 and Baudoin 4 (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Given the specific structure of the intermediate after the conjugate addition step by calculation, it could be found that the distance between the rhodium atom and methylene C–H is quite close due to the N–Rh coordination, which meets the requirement for C–H activation (Scheme B) . To our delight, it would be a novel N-directed α-C­(sp 3 )–H activation as the N atom usually directs β- or γ-C­(sp 3 )–H activation with transition metal catalysts. ,, The valuable product 2aa , containing the 4-phenyl-4,5-dihydro­pyrrole-3-carboxylate unit, was isolated and identified from the quite mixed products along with similar enamine product 3a , conjugate addition products 4aa and 5a (Scheme C), and others. Since 2-pyrroline and 3,4-disubstituted pyrrolidine are the core structure of many pharmacologically active molecules (Scheme D), it could be a useful synthetic strategy considering the convenient availability of 2-(azetidin-3-ylidene) acetates and aryl boronic acids (Scheme E).…”
mentioning
confidence: 95%